2020
DOI: 10.2478/auseb-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure and the Risk: Analysis of Indian Firms

Abstract: Considering the positive relationship between ownership and firm performance in the corporate finance literature, the paper aims to investigate the effect of ownership structure on the risk associated with the firm. Portfolio theories state that an investment with a high return is expected to be associated with high risk; so, it can be argued that ownership should have a positive relation with risk too. However, another explanation is that since large shareholders, such as promoters and financial institutions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…This means that the higher (lower) contestability among major blockholders, the lower (higher) corporate risk (hypothesis 1: accept). These results are similar to previous studies that showed a negative relationship between the ownership structure of blockholder and corporate risk (Admati et al, 1994;Kumari & Kumar, 2020;Rossetto & Staglianò, 2016). This result is similar to the work of Newton and Paeglis (2019) who analysed the relationship between individual blockholder shareholders and systematic risk.…”
Section: The Effects Of Multi-blockholder Contestability and Coalitio...supporting
confidence: 91%
See 3 more Smart Citations
“…This means that the higher (lower) contestability among major blockholders, the lower (higher) corporate risk (hypothesis 1: accept). These results are similar to previous studies that showed a negative relationship between the ownership structure of blockholder and corporate risk (Admati et al, 1994;Kumari & Kumar, 2020;Rossetto & Staglianò, 2016). This result is similar to the work of Newton and Paeglis (2019) who analysed the relationship between individual blockholder shareholders and systematic risk.…”
Section: The Effects Of Multi-blockholder Contestability and Coalitio...supporting
confidence: 91%
“…Rossetto and Stagliano (2016) find a negative relationship between a firm's total risk and ownership of the largest blockholder. Kumari and Kumar (2020) show that there is a negative relationship between ownership and firm-related risk. However, to the best of our knowledge, no empirical analysis has been conducted on the direct impact of blockholder contestability on corporate risk.…”
Section: Literature Review and Hypotheses Development The Relationshi...mentioning
confidence: 96%
See 2 more Smart Citations